(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2025)
Acne vulgaris is a prevalent dermatological disorder affecting adolescents and young adults, with significant psychosocial and emotional consequences. Conventional treatments often have adverse effects, leading to an increasing interest in alternative medicine. This case study explores the therapeutic efficacy of Dawa-e-Musaffi, a polyherbal Unani formulation, in the management of moderate acne vulgaris. A 20-year-old female patient presented with papulo-pustular acne lesions and was treated with Dawa-e-Musaffiin Joshanda formfor40 days. Clinical outcomes were assessed using the Global Acne Grading System (GAGS) and Patient Satisfaction Score (PSS). The results showed a 63.6% reduction in acne severity, a 73.3% reduction in papulo-pustular lesions and a 70% reduction in comedones, and high patient satisfaction, highlighting the potential of Unani medicine as a complementary approach to acne management. Further controlled studies are recommended to validate these findings.